2012
DOI: 10.1007/s00381-012-1753-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of persistent hyperglycemia with outcome of severe traumatic brain injury in pediatric population

Abstract: Early hyperglycemia is associated with poor outcome, and persistent hyperglycemia is a powerful and independent predictor of mortality in children and adolescents with severe TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…In this review, we have summarized the mechanisms leading to hyperglycemia after TBI, including stress response, inflammatory response, diabetes mellitus, pituitary and/or hypothalamic dysfunction, surgery, and anaesthesia. TBI patients with hyperglycemia possess an increased risk of poor outcome and an increased mortality rate, which is more pronounced with persistent hyperglycemia (PH) than hyperglycemia on admission [49]. Some of the direct effects of hyperglycemia may be attributed to lactic acidosis, electrolyte disturbances, inflammation, vessel disorders, rupture of the BBB, and hyperpermeability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, we have summarized the mechanisms leading to hyperglycemia after TBI, including stress response, inflammatory response, diabetes mellitus, pituitary and/or hypothalamic dysfunction, surgery, and anaesthesia. TBI patients with hyperglycemia possess an increased risk of poor outcome and an increased mortality rate, which is more pronounced with persistent hyperglycemia (PH) than hyperglycemia on admission [49]. Some of the direct effects of hyperglycemia may be attributed to lactic acidosis, electrolyte disturbances, inflammation, vessel disorders, rupture of the BBB, and hyperpermeability.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients who subsequently had an unfavorable outcome had higher glucose levels (>200 mg/dL or>11mmol/L) than did those with a better prognosis [11]. In addition, the relationship between high blood glucose levels and poor outcome after TBI appears to be more pronounced with persistent hyperglycemia (PH) than solely hyperglycemia on admission [49]. One study showed that PH was an independent predictor of clinical outcome in severe TBI, and PH was associated with higher mortality rates in patients with severe TBI [50].…”
Section: Hyperglycemia and Clinical Outcomes After Traumatic Brain Inmentioning
confidence: 99%
“…Second, as indicated, we generally withhold glucose in the initial 48 hours after injury while closely monitoring blood glucose concentration [18]. In the survey referenced earlier [36], this approach is taken at ~ 30% of pediatric TBI centers likely given the long-recognized concerns in animal models and patients regarding hyperglycemia in the injured brain [43, 44]. However, we also recognize that the impact of withholding glucose on MEE in children with severe TBI remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…This is just like glucose control in TBI. Lots of studies determine that hyperglycemia is an independent risk factor for TBI [14], [15], [16], [17], [18], [19], but it does not mean that to reduce the glucose level will improve prognosis [20], [21], [22], [23]. Similarly, albumin supplement for patients of TBI is another problem researchers should investigate.…”
Section: Discussionmentioning
confidence: 99%